2012
DOI: 10.1111/joss.12002
|View full text |Cite
|
Sign up to set email alerts
|

Willingness‐to‐Pay for a Nutraceutical‐Rich Juice Blend

Abstract: As human life expectancy increases, the potential for nutraceutical products expands. Economic theory and sensory science were integrated to determine (1) consumer acceptance of potential health statements about a juice blend and (2) the relative satisfaction consumers derived from sensory and nutraceutical characteristics of a juice blend. Four nonhypothetical experimental auction sessions with 11–12 consumers/session were held (n = 47) to elicit willingness‐to‐pay (WTP) for an optimized juice blend (87% Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…These previous studies did not have priming statements of any type presented to consumers. Lawless and others () reported that consumers exhibited higher willingness to pay for nutraceutical juices when given positive priming statements after tasting the beverages. Additionally, when given information about great brands of champagne versus middle or low‐priced brands, consumers had a distinct preference for great brand champagnes whereas when the champagnes were tasted blind, there was no distinct preference (Lange and others ).…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies did not have priming statements of any type presented to consumers. Lawless and others () reported that consumers exhibited higher willingness to pay for nutraceutical juices when given positive priming statements after tasting the beverages. Additionally, when given information about great brands of champagne versus middle or low‐priced brands, consumers had a distinct preference for great brand champagnes whereas when the champagnes were tasted blind, there was no distinct preference (Lange and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment group 1 (Info) received a potential health statement written based on a previous research on a functional juice blend, “This juice blend is rich in polyphenolic antioxidants, which are thought to support health” (Lawless et al . ). The statement was written to indicate that the literature suggests, but does not prove, the described benefit.…”
Section: Methodsmentioning
confidence: 97%
“…, ; Lawless et al . ); however, great potential exists to expand sensory analysis in WTP studies. Specifically, the combined use of sensory evaluation and nonhypothetical valuation tasks to understand product diagnostics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers were also WTP more for organic beef. Lawless and others () used auctioning to determine consumers WTP for a Concord grape and blackberry juice blend with a benefit statement about anthocyanins before (or after) tasting depending on the study group. Reading the health statement after tasting increased WTP more so than reading the health statement prior to tasting.…”
Section: Cost/price—wtpmentioning
confidence: 99%